Improvement vehicle starting system through user password - Mohd Afize Syafri, Mohd Ajwi (2009)
Nowadays, security system has already become one of the important device for each people as a protection for their asset. Security system as a form of protection are structures and processes that provide or improve security as a condition. The ease of control and excellent performance of the password programming will ensure that the number of applications using them will continue grow for the foreseeable future. This project is mainly concerned on improving vehicle starting system by using password program. A program in Borland C++ was developed to provide a protection for the user’s vehicle. User must enter their password first before start the engine. For this application, this project need to use L298N drive motor. The drive motor will receive the signal form the password that user insert in the program then allow the current to flow in the circuit. The motor will turn on if the user insert the password correctly.Besides that, the motor will not turn on. Through the project, it can be concluded that L298N drive motor can control motor to turn on or not based on the effectiveness password program.